Substitution of Polyamide Multifilament by Polyethylene Twisted Monofilament in Large Mesh Gill Nets - Thomas, Saly N.; C., Hridayanathan (Fishery Technology, 2025)
Polyamide (PA) multifilament continues to be the material for gill nets for large pelagics in Kerala despite its replacement by PA monofilament and polyethylene (PE) multifilament in many other states of the country. The cost of the gear contributes significantly to the total investment of the fishing unit viz., around 19% in the mechanised sector and 50% in the motorised sector. Results of a study on replacement of costly PA multifilament by cheaper PE without compromising on the production efficiency are discussed in the present communication. Fishing trials using nets of PE of 1.25 mm dia in comparison to PA 210 dx6x3 (R 455 tex) showed no significant difference in catch and the species composition was similar in both the nets. PE net was found to be cost effective than the PA net, the PE net costing only 52.4% of the PA net. Results indicated that PE twisted monofilament of 1.25 mm dia can be considered for replacement of PAR 455 tex in gill nets for seer and tuna.